FAKTOR-FAKTOR YANG MENENUTUKAN KONSUMEN DALAM MEMILIH CAFE CELEBES WALET 88 DI KOTA PALU - OKTAVIANI, CLARA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
The purpose of this study is to find out what factors determine consumers in choosing the 88 Celebes Walet cafe in Palu City. Types of Explorative research, namely research carried out because this study tries to explore information or problems that are relatively new. In this study researchers used a sample of 72 respondents. The sampling technique used in this study was accidental sampling. The data analysis method used in this study uses factor analysis. The results of this study indicate that there are 5 (five) factors that determine consumers in choosing the 88 Celebes Walet cafe in Palu City. The five factors are factor 1, factor 2, factor 3, factor 4 and factor 5 which is the result of 18 variables analyzed.